2008
DOI: 10.7589/0090-3558-44.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Defenses in the Salamander, Ambystoma Tigrinum, Against Emerging Amphibian Pathogens

Abstract: ABSTRACT:Skin peptides were collected from living Ambystoma tigrinum larvae and adults and tested against two emerging pathogens, Batrachochytrium dendrobatidis and the Ambystoma tigrinum virus (ATV), as well as bacteria isolated from A. tigrinum. Natural mixtures of skin peptides were found to inhibit growth of B. dendrobatidis, Staphylococcus aureus, and Klebsiella sp., but activity against ATV was unpredictable. Skin peptides collected from salamanders held at three environmentally relevant temperatures dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…For a second assay we diluted the most active extracts in sterile distilled water to 5% and 2.5% final concentrations in the zoospore/TGhL mixture. Bd densities at Day 0 and Day 2 were recorded using a Titertek Multiscan Plate Reader at 492 nm, and wells were also observed using an inverted microscope (Sheafor et al 2008). Because plant extracts alone led to darkening of TGhL, which was detected by the Titertek monitor, readings for extracts with TGhL without zoospores present were subtracted from readings for extracts with zoospores.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…For a second assay we diluted the most active extracts in sterile distilled water to 5% and 2.5% final concentrations in the zoospore/TGhL mixture. Bd densities at Day 0 and Day 2 were recorded using a Titertek Multiscan Plate Reader at 492 nm, and wells were also observed using an inverted microscope (Sheafor et al 2008). Because plant extracts alone led to darkening of TGhL, which was detected by the Titertek monitor, readings for extracts with TGhL without zoospores present were subtracted from readings for extracts with zoospores.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Secretion of cationic antimicrobial peptides may decrease the pH of the skin to create a hostile micro-environment. Lower pH on the dorsal surface, particularly during peptide discharge, may be a factor limiting infection there (Weldon & Du Preez 2006, North & Alford 2008, Sheafor et al 2008. Here, higher pH on the ventral surface with higher Bd loads may be a cause or consequence of infection.…”
Section: Mandipropamidmentioning
confidence: 99%
“…Viral mRNA is detectable in the intestines of larval and adult African clawed frogs ( Xenopus laevis ) as early as 3 h after exposure to virus in water and then spreads to other tissues, suggesting that the intestines are a primary point of entry of waterborne virus in amphibians (Robert et al 2011 ). The skin may not be a common site of infection in metamorphosed amphibians because they secrete antimicrobial peptides on their skin, which can inactivate several types of pathogens, including FV3 and ATV (Chinchar et al , 2004Sheafor et al 2008 ; Rollins-Smith 2009 ). Brunner et al ( 2007 ), however, demonstrated that a 1 s skinto-skin contact out of water was suffi cient for transmission of ATV from infected, symptomatic tiger salamander larvae to uninfected larvae, so entry through the epithelium is possible at least during the larval stage.…”
Section: Ranavirus Transmission Within a Speciesmentioning
confidence: 99%